2018
DOI: 10.1016/j.clbc.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation of Breast Cancer: A Retrospective Study

Abstract: RFA in breast cancer is a safe and promising minimally invasive treatment for tumors ≤ 2 cm in diameter. Further studies are needed to optimize the technique and evaluate its future role as local therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 31 publications
0
27
1
4
Order By: Relevance
“…Among them, the most reported is RFA. Ito et al reported that 386 patients treated with RFA at 10 centers from 2003 to 2009 had a 5-year intra-breast recurrence-free rate of 97% for sizes ≤ 1.0 cm, 94% for 1.1 to 2.0 cm, and 87% for > 2.0 cm or more, respectively [16]. Nguyen et al [17] reviewed 30 studies, 643 cases of RFA and reported that complete ablation rates ranged from 100 to 44% with a median of 88%.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the most reported is RFA. Ito et al reported that 386 patients treated with RFA at 10 centers from 2003 to 2009 had a 5-year intra-breast recurrence-free rate of 97% for sizes ≤ 1.0 cm, 94% for 1.1 to 2.0 cm, and 87% for > 2.0 cm or more, respectively [16]. Nguyen et al [17] reviewed 30 studies, 643 cases of RFA and reported that complete ablation rates ranged from 100 to 44% with a median of 88%.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal ablation is already used in clinical practice for primary and metastatic malignant liver, breast, renal, bone and lung tumors [20][21][22][23] but is not yet regularly used for TNs, despite their validation in Korean and Italian studies [24][25][26][27][28]. Radiofrequency ablation (RFA), and laser ablation have already been studied separately for the treatment of benign TNs [29][30][31][32][33][34] and in many retrospective and some prospective comparative studies with a long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy, radiotherapy, and immunotherapy are recommended for the treatment of BC patients with metastatic disease. Although great progresses (including the discovery of novel therapeutic targets and the understanding of mechanisms of resistance to treatment) have been made for the management of patients with metastatic BC, the disease remains incurable, which causes at least half a million deaths related to the disease per year [ 6 11 ]. Therefore, it is important to develop novel prognostic markers associated with clinical outcomes of BC patients and to develop targeted agents that disrupt specific biological processes critical to growth of cancer cells.…”
Section: Introductionmentioning
confidence: 99%